Insulin-like growth factor 1 predicts decompensation and long-term prognosis in patients with compensated cirrhosis - Saeki, Chisato; Kanai, Tomoya; Ueda, Kaoru; Nakano, Masanori; Oikawa, Tsunekazu; Torisu, Yuichi; Saruta, Masayuki; Tsubota, Akihito (Frontiers in Medicine, 2023)
Aim Insulin-like growth factor 1 (IGF-1), which is primarily produced in hepatocytes and is associated with liver functional reserve, plays a crucial role in the pathological condition of cirrhosis. This study aimed to investigate the usefulness of serum IGF-1 levels for predicting the long-term prognosis and decompensation development in patients with cirrhosis. Methods We retrospectively evaluated 148 patients with cirrhosis and divided them into three groups according to baseline IGF-1 levels: low (L)-, intermediate (I)-, and high (H)-IGF-1 groups. The cumulative survival rates were compared among these groups in compensated and decompensated cirrhosis, respectively. Significant and independent factors associated with mortality and decompensation development were identified using Cox proportional hazards regression analysis. Results The median observation period was 57.1 (41.7–63.2) months. Thirty (20.3%) patients died of liver disease-related events and 21 (22.3%) patients with compensated cirrhosis developed decompensation. Multivariate analysis identified low serum IGF-1 levels as a significant and independent factor associated with mortality (all patients: hazard ratio [HR], 0.967; p = 0.004; patients with compensated cirrhosis: HR, 0.927; p = 0.002). The cumulative survival rates were significantly lower in the L-IGF-1 group than in the H-IGF-1 and I-IGF-1 groups (all patients: p < 0.001 and = 0.009; patients with compensated cirrhosis: p = 0.012 and 0.003, respectively). However, in decompensated cirrhosis, the cumulative survival rates demonstrated no significant differences among the three groups. The cumulative decompensation incidence rates were significantly higher in the L-IGF-1 group than in the H-IGF-1 and I-IGF-1 groups (p < 0.001 and = 0.009, respectively). Low serum IGF-1 levels were significantly and independently associated with decompensation development (HR, 0.939; p < 0.001). Conclusion Low serum IGF-1 levels were significantly and independently associated with decompensation development and poor long-term prognosis in patients with compensated cirrhosis. Therefore, IGF-1 may be useful for predicting decompensation-related events and should be regularly monitored in the management of compensated phase.